The Development of Indonesia As The Rule of Law Based On 1945 Constitution Before And After Amendments - Bambang Panji Gunawan; Surti Yustianti; Mohammad Roesli; Bastianto Nugroho (Faculty of Law, Merdeka University Surabaya, Indonesia, 2020)
Prior to amendment of the 1945 Constitution, constitutional basis of Indonesia that Indonesia is a state based on law is contained in the preamble of the 1945 Constitution body. Statement that Indonesia is a country of law is also mentioned in the 1945 Constitution explanation. Article 1 (3) of the 1945 Constitution states that